The CAR-HEMATOTOX: ready for prime time - Frenking, Jan; Rejeski, Kai Dannebom (Blood advances, 2025)
In this issue of Blood Advances, de Boer et al1 validate the predictive capacity of the CAR-HEMATOTOX (HT) as a risk model for cytopenias following chimeric antigen receptor T-cell therapy (CAR-T), now termed immune effector cell-associated hematotoxicity (ICAHT),2 as well as for infections and survival. To this end, the authors performed a population-based retrospective study spanning 7 adult CAR-T centers in the Netherlands, comprising a cohort of 245 patients with relapsed/refractory large B-cell lymphoma treated with standard-of-care axicabtagene ciloleucel. As the primary end point, the authors explored associations between continuous or binary HT scores and clinically significant neutropenia, defined as severe neutropenia for at least 14 days postinfusion. Subsequently, the performance of the HT score as a predictor of grade 3 or higher early (day 0-30) and late (day >30) ICAHT and severe infection events, was assessed. Finally, de Boer et al compared progression-free survival (PFS) and overall survival (OS) by HT risk groups. The authors are to be lauded for the compilation and analysis of this granular data set, which can be regarded as a relevant contribution to the field of CAR-T toxicity research and risk prediction and positions the HT score closer to routine clinical application.